Dynamic Kinetic Resolution of Azlactones by Bifunctional Thioureas with α‑Trifluoromethyl or Methyl Groups - Jiménez, Eddy I.; Cantú-Reyes, Margarita; Flores-Ramos, Miguel; Román-Chavarría, Carlos A.; Díaz-Salazar, Howard; Hernández-Rodríguez, Marcos (Synlett, 2022)
The asymmetric ring opening of azlactones via dynamic kinetic resolution (DKR) is investigated by contrasting thioureas incorporating 1-arylethyl substituents against their more acidic trifluoromethylated analogs. All the catalysts under study outperform Takemoto’s thiourea because of the inclusion of an additional chiral center. However, the difference in yield and selectivity between the fluorinated and non-fluorinated catalysts is minimal. We explain this observation by analysis of calculated transition states. Our findings show that the hydrogen bond (HB) between the NH linked to the 1-arylethyl and the negatively charged oxygen in the benzyloxy ion is the longest in the HB network, whereas the HB between the ammonium group and the same oxygen atom is the shortest. Thus, the substituents and the HB donor ability of this chiral fragment attached to the thiourea are not important in the reaction.
Keywords: amino acids; asymmetric catalysis; stereoselectivity; kinetic resolution; asymmetric synthesis